2023
DOI: 10.26900/hsq.1925
|View full text |Cite
|
Sign up to set email alerts
|

The usability of telephone-based telemedicine in primary healthcare: A quantitative evaluation and a hypothesized framework of determinants from the physicians’ perspective in Oman

Abstract: Telemedicine has been appreciated as a smart solution to bridge the gaps in the delivery and coverage of healthcare worldwide. With the great impetus to integrate this service into primary healthcare facilities, evaluating its usability should be an ongoing process. This study aimed to quantitatively evaluate the usability of telemedicine from the primary healthcare physicians’ perspective in Oman. The evaluation was conducted using a cross-sectional study design. A self-administered online questionnaire was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 54 publications
(68 reference statements)
0
10
0
Order By: Relevance
“… 3 Additionally, conducting physical examinations, measurements and lab investigations is impossible in telephone-based consultations. 14 Gharbal et al suggested that incorporating a visual component, such as video calls, instead of telephone-based consultations may enhance the quality of care provided and achieve comparable efficiency to in-person visits. 14 Similar views were expressed by the psychiatrists in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 3 Additionally, conducting physical examinations, measurements and lab investigations is impossible in telephone-based consultations. 14 Gharbal et al suggested that incorporating a visual component, such as video calls, instead of telephone-based consultations may enhance the quality of care provided and achieve comparable efficiency to in-person visits. 14 Similar views were expressed by the psychiatrists in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Gharbal et al suggested that incorporating a visual component, such as video calls, instead of telephone-based consultations may enhance the quality of care provided and achieve comparable efficiency to in-person visits. 14 Similar views were expressed by the psychiatrists in our study. By using video calls, care providers can conduct thorough assessments and identify patients with low, intermediate or high risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations